Segmental Darier’s disease. Case report. - Ingordo, V.; Gigantesco, M.; Colonna, V.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
Darier's disease is an inherited autosomal dominant skin disorder caused by a gene mutation in the 2-cM region of 12q23-q24.1. The disease usually starts in the first two decades of life, although sometimes appearing in older subjects. Clinically, it is characterized by hyperkeratotic papules symmetrically affecting the seborrheic regions, which are deteriorated by ultraviolet radiations. In the relevant literature there are reports of segmental Darier's disease, characterized by skin lesions clinically and histologically superimposable to the generalized disease. Here is reported a segmental case of Darier's disease.